Efficacy and safety of repetitive transcranial magnetic therapy for post-stroke aphasia: a systematic review and meta-analysis of randomized controlled trials - Xie, Lin; Diao, Yingxiu; Gong, Cheng; Huang, Jiahao; Huang, Miao; Dong, Zhenying (Frontiers in Neurology, 2025)
ObjectiveThe purpose of this meta-analysis was to investigate the effectiveness and safety of repetitive transcranial magnetic stimulation (rTMS) in the treatment of patients with post-stroke aphasia (PSA).MethodsThe PubMed, PEDro, Embase, Cochrane Library, CNKI, Wanfang Data and Web of Science databases were systematically searched from inception until January 30, 2024. Eligible randomized controlled trials (RCTs) contained information on the population (PSA), intervention (rTMS), and outcomes (Western Aphasia Battery, Aphasia Quotient, Aphasia Battery in Chinese, Boston Diagnostic Aphasia Examination, Aachener Aphasie Test, Concise Chinese Aphasia Test and Computerized Picture Naming Test). Participants in the rTMS intervention group were compared with those in sham or other control groups. Two independent researchers searched for, screened, and qualified the articles. Two independent researchers extracted key information from each eligible study. The authors’ names, year of publication, setting, total sample size, rTMS parameters, baseline/mean difference (MD), and 95% confidence interval (CI) were extracted using a standardized form, and the methodological quality was assessed using the Cochrane Risk of Bias tool (Revman 5.40, Nordic Cochrane Center) and GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) system.ResultsThirty relevant RCTs were included, involving a total of 1,597 patients. The analysis turned out that rTMS combined with speech and language therapy (SLT) resulted in significant improvements in auditory comprehension, naming, repetition, and spontaneous speech in patients with PSA compared with sham stimulation combined with SLT or SLT alone in the control group. (auditory comprehension, MD = 1.94, 95%CI = [1.16, 2.17], p < 0.001; naming, MD = 1.53, 95%CI = [0.82, 2.24], p < 0.001; repetition, MD = 1.79, 95%CI = [1.20, 2.38], p < 0.001; spontaneous speech, MD = 1.97, 95%CI = [1.65, 2.29], p < 0.001).ConclusionThis meta-analysis showed that rTMS can safely and effectively promote the recovery of speech function in patients with PSA.Clinical trial registrationThe study has been registered with Prospero https://www.crd.york.ac.uk/PROSPERO/search, (CRD42022363899).